The Effect of Consuming Stevia Liquid Extract (Steviol Glycosides) on Reducing Blood Sugar Levels in Patients With Type 2 Diabetes Mellitus - Eko Hermanto; Try Pratama Nugraha; Yulidian Pratiwi; Mila Sartika; Aprilina Sartika (Jurnal Multidisiplin Sahombu, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by high blood sugar levels due to impaired insulin production or use. The global prevalence of DM in 2021 reached 10.5% and is projected to increase to 12.2% by 2045. In Indonesia, the prevalence of DM in 2021 was recorded at 10.8% or around 19.5 million cases, while in Bekasi Regency, the prevalence of T2DM in 2022 reached 8.04% per 100 population. This study aims to evaluate the effect of Stevia (Steviol Glycosides) extract consumption on reducing blood sugar levels in T2DM patients. The research method used a quasi-experiment design with two group pre-post design, involving 76 T2DM patients who were divided into two groups, namely the intervention group given Stevia extract and the control group without treatment. The results of data analysis showed that before the intervention, there was a significant difference in blood sugar levels between the two groups (p = 0.000), with higher blood sugar levels in the intervention group. After the intervention, Stevia extract consumption was shown to significantly reduce blood sugar levels compared to the control group (p = 0.023). The conclusion of this study is that Stevia extract consumption has a significant effect on reducing blood sugar levels in T2DM patients, so it can be considered as a complementary therapy in the management of type 2 DM in the community.